Care processes and structures associated with higher medication adherence in adolescent and young adult transplant recipients. (2nd August 2021) - Dabirzadeh, Anita; Dahhou, Mourad; Zhang, Xun; Sapir‐Pichhadze, Ruth; Cardinal, Heloise; White, Michel; Johnston, Olwyn; Blydt‐Hansen, Tom D.; Tibbles, Lee Anne; Hamiwka, Lorraine; Urschel, Simon; Birk, Patricia; et al.
Abstract: Background: We aimed to identify care processes and structures that were independently associated with higher medication adherence among young transplant recipients. Methods: We conducted a prospective, observational cohort study of 270 prevalent kidney, liver, and heart transplant recipients 14–25 years old. Patients were ≥3 months post‐transplant, ≥2 months post‐discharge, and followed in one of 14 pediatric or 14 adult transplant programs in Canada. Patients were enrolled between June 2015 and March 2018 and followed for 6 months. Adherence was assessed at baseline, 3, and 6 months using the BAASIS © self‐report tool. Patients were classified as adherent if no doses were missed in the prior 4 weeks. Transplant program directors and nurses completed questionnaires regarding care organization and processes. Results: Of the 270 participants, 99 were followed in pediatric programs and 171 in adult programs. Median age was 20.3 years, and median time since transplant was 5 years. At baseline, 71.5% were adherent. Multivariable mixed effects logistic regression models with program as a random effect identified two program‐level factors as independently associated with better adherence: minimum number of prescribed blood draws per year for those >3 years post‐transplant (per 1 additional) (OR 1.12 [95% CI 1.00, 1.26]; p  = .047), and average time nurses spend with patients in clinic (per 5 additional minutes) (OR 1.15 [1.03, 1.29]; p  = .017). Conclusion: Program‐level factors including protocols with a greater frequency of routine blood testing and more nurse time with patients were associated with better medication adherence. This suggests that interventions at the program level may support better adherence.